Faktor Risiko Kesiapan Kehamilan, Perilaku Nurtisi, dan Perilaku Pencegahan sebagai Prediktor Hipertensi Kehamilan - Novi Anggraeni; Riyadatus Solihah; Sitti Mukarramah; Arkha Rosyaria Badrus; Faisal Amir (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Hypertension in pregnancy is a condition of high blood pressure that occurs during pregnancy or is caused by pregnancy itself, and generally occurs after 20 weeks of gestation. This condition is one of the most common complications of pregnancy, with a prevalence of around 5–15%. The mother's readiness for pregnancy, nutritional behavior, and preventive behavior are considered very important in helping to reduce maternal and infant mortality rates, one of which is by maintaining a pregnancy without hypertension. This study aims to analyze pregnancy readiness, nutritional behavior, and preventive behavior in relation to the occurrence of pregnancy-induced hypertension. The research method used an observational analytical approach with a cross-sectional study design. The sample consisted of 71 pregnant women selected through accidental sampling. The research instruments used questionnaires and a sphygmomanometer, and the collected data were analyzed using the Spearman rank correlation test. The results showed that pregnancy readiness was associated with the occurrence of pregnancy-induced hypertension, with a p-value of 0.039 and a correlation coefficient of -0.246, while nutritional behavior and the occurrence of pregnancy-induced hypertension showed a p-value of 0.010 and a correlation coefficient of -0.306, and preventive behavior and the occurrence of pregnancy-induced hypertension showed a p-value of 0.046 and a correlation coefficient of -0.238. The conclusion of this study is that there is an influence of pregnancy readiness on the occurrence of pregnancy-induced hypertension, there is an influence of nutritional behavior on the occurrence of pregnancy-induced hypertension, and there is an influence of preventive behavior on the occurrence of pregnancy-induced hypertension. Keywords: Hypertension; Pregnancy; Nutrition; Prevention; Behavior.